Organic residue analysis of Early Neolithic 'bog pots' from Denmark demonstrates the processing of wild and domestic foodstuffs. (April 2021) - Robson, Harry K.; Saul, Hayley; Steele, Valerie J.; Meadows, John; Otto Nielsen, Poul; Fischer, Anders; Heron, Carl P.; Craig, Oliver E.
Highlights: This study explores the use of Early Neolithic 'bog pots' intentionally deposited into wetlands. We combine organic residue analysis alongside Bayesian chronological modelling. We consider 34 Early-Middle Neolithic (c. 3900–2350 cal BC) vessels from Denmark. The results show that the vessels had been used to process both wild and domesticated foodstuffs. Our Bayesian chronological model shows that Koch's (1998) Funnel Beaker Types form a sequence. Abstract: Ceramic containers, intentionally deposited into wetlands, offer detailed insights into Early Neolithic culinary practices. Additionally, they are key for ascertaining the Neolithisation process in Denmark since they appear to form a typo-chronological sequence. Here, we use a combination of organic residue analysis (ORA) of pottery alongside Bayesian chronological modelling of the radiocarbon dates obtained on these vessels to explore the initial stages of votive deposition in wetlands, a practice that stretches from the Mesolithic to the onset of Christianity in Northern Europe. We consider 34 Early-Middle Neolithic (c. 3900–2350 cal BC) 'bog pots' from Denmark, of which 20 have ORA data, and 26 have been dated directly. Carbonised surface residues and absorbed lipids from powdered sherds were analysed using a combination of bulk carbon and nitrogen stable isotope analysis, gas chromatography-mass spectrometry (GC–MS) and GC-combustion-isotope ratio MS (GC-C-IRMS). The molecular and isotopic compositions of the analysed samples revealed the presence of aquatic, ruminant carcass and dairy fats as well as plant waxes with the majority containing mixtures thereof. Dairy fats were present from the onset of the Funnel Beaker culture, whilst aquatic foods, prevalent at the close of the preceding Mesolithic period, continued to be processed in pottery for the following thousand years.